2023
DOI: 10.1021/acsami.2c20878
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Oxide Nanozymes with Multiple Enzyme-Mimic Activities for Tumor Catalytic Therapy

Abstract: Using tumors containing high concentrations of hydrogen peroxide to design nanozymes is a new and effective strategy, and vanadium-based nanomaterials receive increasing attention. In this paper, four kinds of vanadium oxide nanozymes with different valences of vanadium are synthesized by a simple method to verify the effect of valence on enzyme activity. Vanadium oxide nanozyme-III (Vnps-III) with a low valence of vanadium (V4+) exhibits good peroxidase (POD) and oxidase (OXD) activities, which can effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…, V–O and V–N. 24 The two main peaks at 132.46 eV and 133.22 eV corresponded to P 2p 3/2 and P 3p 1/2 25 (Fig. 2d).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…, V–O and V–N. 24 The two main peaks at 132.46 eV and 133.22 eV corresponded to P 2p 3/2 and P 3p 1/2 25 (Fig. 2d).…”
Section: Resultsmentioning
confidence: 96%
“…23 The higher binding energy (BE) (Fig. 2c) of V IV 2P at 516.02 eV (V IV 2P 3/2 ) and 523.84 eV (V IV 2P 1/2 ) indicated different chemical environments of V IV i.e., V-O and V-N. 24 The two main peaks at 132.46 eV and 133.22 eV corresponded to P 2p 3/2 and P 3p 1/2 25 (Fig. 2d).…”
Section: Characterizationmentioning
confidence: 99%
“…The modulation of atomic valence state not only enabled the fine-tuning of nanozyme activity but also influenced the enzyme-like properties of nanozymes. Li and colleagues synthesized a series of vanadium oxide nanozymes (Vnps-x, where x = I, II, III, IV) and demonstrated that Vnps-III containing V 4+ valence exhibited POD and OXD activities, while Vnps-I with V 5+ valence displayed CAT activity . Ultimately, by controlling the V 4+ /V 5+ ratio, one can successfully prepare Vnps with combined POD, OXD, and CAT activities.…”
Section: Catalytic Mechanismsmentioning
confidence: 99%
“…6 To conquer these limitations, enormous strategies have been developed including direct delivery of O 2 to the tumor site, 7 oxygen production in situ, 8 or conversion of excess endogenous hydrogen peroxide (H 2 O 2 ) to O 2 . 9 Nevertheless, these strategies cannot fundamentally address the issues of oxygen dependence. In recent years, the ability of some azo-based initiators to generate alkyl radicals in the absence of oxygen upon thermal stimulation has attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these anticancer modalities are oxygen-dependent, and the hypoxic tumor microenvironment in solid tumors considerably limits their treatment efficacy . To conquer these limitations, enormous strategies have been developed including direct delivery of O 2 to the tumor site, oxygen production in situ, or conversion of excess endogenous hydrogen peroxide (H 2 O 2 ) to O 2 . Nevertheless, these strategies cannot fundamentally address the issues of oxygen dependence.…”
Section: Introductionmentioning
confidence: 99%